COVID-19 and gender inequality in the labor market the Philippine experience - Bautista, Keisha Aeris C.; Retardo, Janell R.; Mendoza, Adrian (Quezon City School of Economics, University of the Philippines Diliman, 2022)
This study examines whether COVID-19 exacerbated the existing gender gaps in the Philippine labor market. Using the Labor Force Surveys for October 2019 and October 2020, we perform probit regressions and post-estimation tests to compare the labor market experience of men and women before and during the pandemic. Three key indicators of labor market activities are analyzed: labor force participation, employment, and decision not to work due to household responsibilities. These outcomes are then assessed against a set of household-related characteristics such as marital status, having young children, and being a household head. The results confirm that significant gender gaps persist in terms of the contribution of the household-related determinants in men and women’s probability of labor force participation and employment during the pandemic. For instance, having young children has contrasting effects on men's and women’s labor market activities: positive for men but negative for women. Further the results confirm the gender bias in terms of the decision not to work or look for work due to family duties. Being married and having young children significantly increase women’s probability of performing unpaid household work, while there is no similar evidence for men. On a positive note, our results do not provide evidence that COVID-19 exacerbated the gender gaps in terms of the contribution of household-related variables to labor force participation, employment, and performance of unpaid household work.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: COVID-19 Pandemic; Gender inequality -- Philippine labor market